2020
DOI: 10.3892/mmr.2020.11058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulation on cell activity, cell cycle, cell apoptosis and β‑catenin pathway in the injured dorsal root ganglion cell

Abstract: The present study aimed to investigate the effects of electrical stimulation (eS) on cell activity, cell cycle and apoptosis in injured rat dorsal root ganglion (drG) cells induced by cyclic mechanical stretching (cMS). The present study also investigated whether the Wnt/β-catenin pathway is involved in this process. injury and eS models were established in drG cells. Then, cell activity was detected using a cell counting Kit-8 and 5-ethynyl-2'-deoxyuridine-594 cell proliferation assay kit. cell cycle distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Hu et al have recently demonstrated that ES could significantly promote the proliferation activity of dorsal root ganglion cells (DRGs) and inhibited cell apoptosis. The results of this study also showed that ES could activate the Wnt/ β -catenin signaling pathway and exert a protective effect on the injured DRGs [ 43 ]. Recently, it has been reported that ES increases the expression of mRNA of brain-derived neurotrophic factor (BDNF) and consequently its protein level in the Müller cell in vitro [ 44 ].…”
Section: The Effect Of Es On the Ocular Cell In Vitro And In Vivomentioning
confidence: 96%
“…Hu et al have recently demonstrated that ES could significantly promote the proliferation activity of dorsal root ganglion cells (DRGs) and inhibited cell apoptosis. The results of this study also showed that ES could activate the Wnt/ β -catenin signaling pathway and exert a protective effect on the injured DRGs [ 43 ]. Recently, it has been reported that ES increases the expression of mRNA of brain-derived neurotrophic factor (BDNF) and consequently its protein level in the Müller cell in vitro [ 44 ].…”
Section: The Effect Of Es On the Ocular Cell In Vitro And In Vivomentioning
confidence: 96%
“…To exclude possible cytotoxic effects, it is necessary to prove cell viability and proliferative activity after ES, which can be performed via fluorescent imaging (Live/Dead, Calcein AM, EdU) or metabolic assays (CCK-8, AlamarBlue etc.) [ 112 ]. The direct effect of electrical stimulation on the cell membrane should be monitored using VGCC inhibitors, while the creation of micropores can be proved via the Yo-Pro-1 uptake [ 113 ].…”
Section: Recommendations On Reporting Es In the Context Of Chondrogen...mentioning
confidence: 99%
“…This can limit the effectiveness of the hydrogels in promoting axonal growth. Recent studies , reported that electrical fields may direct axonal growth by influencing various signaling pathways and cellular processes. This guidance can facilitate the axons to grow through the glial scars’ border or inhibit GFAP positive cell marker expression that reduces the glial cell proliferation at the injury site. , …”
Section: Introductionmentioning
confidence: 99%